201 killer cover letters - Podesta, Sandra (McGraw-Hill Education, 2014)
"For anyone applying for a job, networking, requesting a reference, or writing a thank-you letter, this new edition of the go-to guide addresses new developments in technology and communication and how they affect the cover letter writing process"--